Social Supervision Behavioral of the Village Income and Expenditure Budget Reaches Welfare Windu Kencana in Indonesia - Prasetyo, Whedy (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
Purpose: This research aims to show social supervision policy in the implementation of IEB in Indonesia. Methodology: Descriptive qualitative study with case study approach. Open interview was conducted to reveal the accountability and response of the community for the IEB Village. This kind of interaction was carried out for five months from 09 March to 10 August 2024 is Abdul Halim Iskandar (Minister of Villages, Development of Disadvantaged Regions and Transmigration of the Indonesia Republic) and Taufik Madjid (Secretary General of the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration). Finding: The results show that the community supervision in IEB has a direction to fulfill the needs and expectations of the community. This atmosphere has the potential to produce the exact percentage of use and affirmative programs as well as a communication medium that can reduce the potential for conflict. Openness in running IEB Village make interaction is like brother and not push each other. The mystique of togetherness produces reflective rationality thinking of the village officials in dealing with its citizens. Implication: The manifestation of harmonious social relationships that reflect a peace sense, and produce a prosperity sense and harmony together. Conditions for realization of social supervision by contributing to transparency, accountability, participation and order. This belief is a just, prosperous and prosperous [windu kencana] manifestation without any deviation in its implementation. Originality: Manifestation of windu kencana as a result to social supervision policy is a form of control or assessment to determine the implementation of activities in accordance with established plans (IEB Village). This situation proves the active involvement in the IEB Village management.